Rove exposed : - Moore, James (Wiley, 2006)
Veteran journalists Moore and Slater offered a glimpse into Karl Rove's singular influence within the Bush administration in their best-selling Bush's Brain, and in light of the recent contretemps in Washington, the authors have issued this deftly reported revision of their earlier book. The title of this up-to-date foray into the machinations of "Bush's Brain" belies the book's incredible depth; revealing not only the details of Rove's success and failures, the book also directs a critical eye toward his Salt Lake City childhood, his earliest political ambitions and the events that shaped his values. Broader than an exposé, but too partisan and brief to be considered a full-fledged biography, the book portrays a man "not beyond lying" and obsessed with "creating power and winning elections" whose character is governed by a simple ethos: to succeed at any cost (even when the battle at hand is a questionably good-natured snowball fight with reporters). Moore and Slater are quick to acknowledge Rove is, for better or worse, very good at his job, and provide ample analysis of "Roverian" politics (or, "Rovian Cancer," as the authors put it) from his days advising state-level campaigns to the build-up to, and ongoing fallout from, the invasion of Iraq. A piercing examination of the preeminent right wing political strategist, the book will find favor among politics buffs.